2001
DOI: 10.1095/biolreprod65.4.1020
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Follicle-Stimulating Hormone and Growth Factors in Modulating Secretion of Steroids and Inhibin-Related Peptides by Nonluteinized Bovine Granulosa Cells1

Abstract: The aim was to investigate potential interactions between FSH and intraovarian growth factors in modulating secretion of inhibin A (inh A), activin A (act A), follistatin (FS), estradiol (E2), and progesterone (P4) by bovine granulosa cells cultured under conditions in which a nonluteinized FSH-responsive phenotype is maintained. Cells from 4- to 6-mm follicles were cultured in serum-free medium containing insulin (10 ng/ml) and androstenedione (10(-7) M), and effects of ovine FSH (0.037-3 ng/ml) were tested a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
104
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(119 citation statements)
references
References 68 publications
13
104
0
2
Order By: Relevance
“…It seems likely that the intrafollicular balance between inhibin, activin and its binding protein FS is important in determining follicular response to these proteins (Findlay et al 2001, Knight & Glister 2001. However, while the present study has clearly shown that such changes occur, it is not possible to assess whether these merely reflect, rather than contribute to, the process(es) which drive follicles through specific developmental checkpoints during folliculogenesis.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…It seems likely that the intrafollicular balance between inhibin, activin and its binding protein FS is important in determining follicular response to these proteins (Findlay et al 2001, Knight & Glister 2001. However, while the present study has clearly shown that such changes occur, it is not possible to assess whether these merely reflect, rather than contribute to, the process(es) which drive follicles through specific developmental checkpoints during folliculogenesis.…”
Section: Discussionmentioning
confidence: 54%
“…) are present in the ovaries of most mammalian species examined (Knight & Glister 2001). mRNAs encoding inhibin/activin -, A-and B-subunits are also detectable in chicken ovarian follicles (Chen & Johnson 1996, Davis & Johnson 1998 and increasing evidence suggests inhibin-related proteins have important roles in regulating ovarian function in birds.…”
Section: Two Forms Of Inhibin (A ( -A) and B ( -B)) And Three Forms Omentioning
confidence: 99%
See 1 more Smart Citation
“…Granulosa cell secretion of dimeric inhibin A is regulated by FSH (21,22), and increases as the dominant follicle approaches 185 preovulatory status (17,23). In the current study, cows with ovulatory follicles had higher circulating inhibin A compared to cows with non-ovulatory follicles, despite having lower circulating FSH concentrations.…”
Section: Discussion 175mentioning
confidence: 99%
“…IGF-I also increases expression of LH receptors and responsiveness to FSH, which is reported to enhance aromatase production in the in vitro culture of mouse, sheep, and pig GCs (1,37,39). IGF-I has also been reported to increase the expression of estradiol in GCs (14). Conversely, in 2000 Khalid et al discovered that estradiol or FSH stimulate synthesis of IGF-I (27).…”
Section: Nsn (Mii(nsn)) or Competent Metaphase Ii-derived Sn (Mii(sn)mentioning
confidence: 99%